2020
DOI: 10.1523/eneuro.0463-20.2020
|View full text |Cite
|
Sign up to set email alerts
|

Time-of-Day-Dependent Gating of the Liver-Spinal Axis Initiates an Anti-Inflammatory Reflex in the Rat

Abstract: The autonomic nervous system (ANS) modulates the immune response through the engagement of an anti-inflammatory reflex. There is controversy regarding which efferent branch of the ANS, sympathetic or parasympathetic, downregulates the intensity of the inflammatory response. Furthermore, how information about the immune status of the body reaches the CNS to engage this reflex remains unclear. The present study demonstrates the existence of a liver-spinal axis that conveys early circulating inflammatory informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 58 publications
0
6
1
Order By: Relevance
“…Our data showed that rats with the hepatic sympathetic nerves severed responded to intravenous LPS with IL-10 and TNF levels no different to those of sham-operated animals [ 34 ], indicating that these nerves are not necessary for the acute reflex control of systemic inflammation. These results deviated from those reported by Soto-Tinoco and colleagues, where animals with denervated livers responded to LPS with an exaggerated TNF release [ 54 ]. It is likely that several differences in experimental approach underlie these discrepancies.…”
Section: The Gastro-intestinal Tract a Key Physiological System For I...contrasting
confidence: 99%
See 1 more Smart Citation
“…Our data showed that rats with the hepatic sympathetic nerves severed responded to intravenous LPS with IL-10 and TNF levels no different to those of sham-operated animals [ 34 ], indicating that these nerves are not necessary for the acute reflex control of systemic inflammation. These results deviated from those reported by Soto-Tinoco and colleagues, where animals with denervated livers responded to LPS with an exaggerated TNF release [ 54 ]. It is likely that several differences in experimental approach underlie these discrepancies.…”
Section: The Gastro-intestinal Tract a Key Physiological System For I...contrasting
confidence: 99%
“…While extensive research work has been done on the pathways composing the efferent arm of the inflammatory reflex, much less is known about the afferent arm and the central integrative pathways. Recent studies have described the important contributions of the carotid body and of a liver-spinal axis as possible sensory arms of the inflammatory reflex [ 54 , 58 ]; however, the contributions from the vagus nerve and circulating humoral factors, including immune cells and their by-products, also need to be considered. Further, studies are necessary to delineate the inflammatory reflex and understand how the sympathetic nervous system is involved in the check and balance mechanisms that characterize immune responses, acute and chronic, involving innate and adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Experiments where the sympathetic nerves to the liver were removed (and its vagal innervation also removed by vagotomy) showed no evidence for their involvement in the regulation of either TNF or IL‐10 responses to systemic LPS (Figs 7 and 8). This result was surprising, in view of the recent demonstration by Soto‐Tinoco and colleagues that spinal afferent fibres in the hepatic sympathetic nerves support an early anti‐inflammatory reflex response to systemic LPS (Soto‐Tinoco et al., 2020). Several differences in experimental approach may account for this discrepancy: here, we used a higher dose of systemic LPS (60 vs .…”
Section: Discussionmentioning
confidence: 93%
“…Section of the hepatic sympathetic nerves has previously been reported to enhance TNF levels in endotoxaemic rats, an effect attributed to interrupting transmission in afferent fibres to the spinal cord (Soto‐Tinoco et al., 2020). In vagotomized animals, we therefore cut the hepatic sympathetic nerves (which include the spinal afferent supply, completing liver denervation), and compared these with vagotomized animals given sham hepatic nerve section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation